A COMPARATIVE STUDY OF MARRIAGE CEREMONIES AMONG KASHMIRI PANDITS AND KASHMIRI MUSLIMS - Shabir Ahmad Dar; Dr. J. Muthukumar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
ABSTRACT Hindus and Muslims have coexisted harmoniously when Islam became the predominant religion in Kashmir since 13th century. The Sufi-Islamic way of life of Kashmiri Muslims and the Rishi tradition of Kashmiri Hindus coexisted and complemented one another, forming a separate ethnic group in which both have some common customs. In Kashmir, the customs surrounding marriage are intriguing. The major events that occur in marriage are the same. It is evident that there are numerous similarities between the rites of Kashmir's Muslims and Hindus, such as the special significance of salt and walnuts and the use of mehendi dye. Both faiths have the Laganchir, Phirsal, Gulmuith, the attire and titles of the Maharaz and Maharein, among other things, in addition to the use of Mehendidye. The goal of the current study is to investigate the historical backdrop of the marriage system used by Muslims and Kashmiri gurus. However, the article's main focus has been on how marriage customs have evolved over time.